Regulatory Issues on Tender Offers Leading to Delisting in the Philippine Stock Market - Cayanan, Arthur (Philippine Management Review; Vol 27 (2020), 2021)
This paper discusses three cases of tender offers in the Philippines that led to delisting. These are Liberty Telecoms Holdings, Incorporated (LIB), Melco Resorts and Entertainment (Philippines) Corporation (MRP), and Travellers International Hotel Group, Incorporated (RWM), operator of Resorts World Manila. This paper examines the regulatory issues on tender offers, and how they affect minority stockholders.